Digital hygiene of schoolchildren: how to teach internet safety from an early age - Király Dominik; Stoika Myroslav; Sztojka Miroszláv; Стойка Мирослав (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Digital hygiene is a set of norms, skills, and habits that ensure safe, healthy, and conscious use of digital technologies. Schoolchildren, especially younger ones, are a vulnerable group due to their insufficiently developed critical thinking, socio-emotional characteristics, and inexperience in the digital environment [1]. Teaching internet safety should begin at an early age and progress gradually, taking into account the child’s developmental stage. At first, it is important to teach simple rules — not to share personal information, not to open suspicious links, and not to communicate with strangers — and later move on to more complex topics such as cyberbullying, phishing, fraud, password protection, and privacy [2]. The role of parents and teachers in this process is crucial: they should not only explain the rules but also create a trusting environment where a child can discuss online experiences, report dangerous situations, and receive support [3]. It is essential to develop children’s critical thinking — the ability to question the information they see online, assess the reliability of sources, and recognize manipulation and false content. According to UNICEF, about 95% of children and young people in Ukraine actively verify online information; however, a significant number still encounter cyberbullying or online fraud [4]. At school, teaching digital safety should be systematic and interdisciplinary. This can include integrated lessons, training sessions, role-playing games, projects, or case discussions. Studies show that the use of interactive methods — games, discussions, and online courses — significantly increases students’ awareness and promotes behavioral change in the digital environment [5]. In Ukraine, there are educational initiatives aimed at developing digital hygiene skills, such as the “Cyber Hygiene for Youth” and “Online Safety for Children” courses on the Diia.Education platform, which provide practical advice on protecting personal data, avoiding cyber risks, and using gadgets safely [6; 7].
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital hygiene; schoolchildren; digital technologies